Relationship between plant species diversity and aboveground biomass in alpine grasslands on the Qinghai–Tibet Plateau: Spatial patterns and the factors driving them - Yang, Mingxin; Chen, Ang; Zhang, Min; Gu, Qiang; Wang, Yanhe; Guo, Jian; Yang, Dong; Zhao, Yun; Huang, Qingdongzhi; Ma, Leichao; Yang, Xiuchun (Frontiers in Ecology and Evolution, 2023)
Alpine grasslands are important ecosystems on the Qinghai-Tibet Plateau and are extremely sensitive to climate change. However, the spatial responses of plant species diversity and biomass in alpine grasslands to environmental factors under the background of global climate change have not been thoroughly characterized. In this study, a random forest model was constructed using grassland ground monitoring data with satellite remote sensing data and environmental variables to characterize the plant species diversity and aboveground biomass of grasslands in the Three-River Headwaters Region within the Qinghai-Tibet Plateau and analyze spatial variation in the relationship between the plant species diversity and aboveground biomass and their driving factors. The results show that (1) the selection of characteristic variables can effectively improve the accuracy of random forest models. The stepwise regression variable selection method was the most effective approach, with an R2 of 0.60 for the plant species diversity prediction model and 0.55 for the aboveground biomass prediction model. (2) The spatial distribution patterns of the plant species diversity and aboveground biomass in the study area were similar; they were both high in the southeast and low in the northwest and gradually decreased from east to west. The relationship between the plant species diversity and aboveground biomass varied spatially; they were mostly positively correlated (67.63%), but they were negatively correlated in areas with low and high values of the plant species diversity and aboveground biomass. (3) Analysis with Geodetector revealed that longitude, average annual precipitation, and elevation were the main factors driving variation in the plant species diversity and aboveground biomass relationship. We characterized the plant species diversity and aboveground biomass, as well as their spatial relationships, over a large spatial scale. Our data will aid biodiversity monitoring and grassland conservation management, as well as future studies aimed at clarifying the relationship between biodiversity and ecosystem functions.